PENGARUH KUALITAS KOMUNIKASI, PENEMPATAN, DAN INSENTIF TERHADAP DISIPLIN PERAWAT PSIKIATRI RSUD BANGLI, KECAMATAN BANGLI, KABUPATEN BANGLI, BALI - Ni Nengah Tiastiningsih (Bajang Institute, 2025)
This study aims to analyze the relationship between communication quality, nurse placement, and incentive perception with work discipline among psychiatric nurses at RSUD Bangli, Bali. Psychiatric nursing services require a high level of discipline due to the complexity and risks associated with patient care. This research employed a quantitative cross-sectional design involving 100 psychiatric nurses as respondents. Data were collected using validated instruments, namely the Communication Assessment Tool (CAT), Practice Environment Scale–Nursing Work Index (PES-NWI), incentive perception questionnaire, and nurse discipline questionnaire. Data analysis was conducted using Spearman’s rho correlation test, as several variables did not meet the assumption of normality. The results revealed that communication quality had a positive and significant correlation with nurse discipline (r = 0.485; p < 0.001), nurse placement also showed a positive and significant correlation with discipline (r = 0.523; p < 0.001), and incentive perception was positively associated with discipline (r = 0.352; p < 0.001). Additionally, communication quality was significantly correlated with nurse placement and incentive perception. These findings indicate that improving communication effectiveness, ensuring appropriate nurse placement, and implementing a fair incentive system can collectively enhance work discipline among psychiatric nurses. The study highlights the importance of integrated human resource management strategies in improving service quality and patient safety in psychiatric care settings